Hydraulic Fracturing Mine Back Trials — Design Rationale and Project Status - Kaiser, P.K.; Valley, Benoît; Dusseault, M.B.; Duff, D. (My University, 2013)
Last year, a joint Mining and Oil & Gas industry consortium was established in Canada to conduct hydraulic fracturing (HF) tests accompanied by a mine-back of fractured regions to assess HF models and microseismic monitoring data during controlled experiments. Details about the displacement field, fracture aperture and extent, and micro-seismic parameters could then be verified and used as calibration data for modeling of HF processes in igneous and dense sedimentary rocks. Various injection experiments are planned and they will include pre-fracturing rock mass characterisation using best available current techniques, dense arrays of multi-parameter wall and borehole-mounted instruments, and the treated volume will be mined through to assess fracturing effectiveness, existing fractures and new fracture interactions, and to determine if pathways can be identified for improving currently available numerical and fracture network modeling tools. In this paper we present the results of the experimental design and planning phase, outlining objectives and justifications for planned experimental layouts. Preliminary plans for a first mine-through trial at Newcrest Mining’s Cadia East mine in New South Wales, Austral‐ ia are described. The hypotheses advanced in this experimental design, supported by evidence from the literature, are that activation and development of a fracture network by hydraulic stimulation is possible if the injection procedure is designed such that injection pressures and rates are maintained within an optimal window, thereby producing conditions under which effective stress management for risk mitigation in deep mining can best be achieved. The evaluation of these hypotheses is the focus of the current high level experimental plan presented in the paper.
, 2023
Keywords: stress management; stiffness modification; shale gas analogue; mine-back experiments; model calibration; hydraulic fracture; naturally fractured rocks